Experimental Studies on Domestic Cat as a Definitive Host of Spirometra Species - Nicholas J. Kavana (Contemporary Research and Perspectives in Biological Science Vol. 3, 2024)
In the present study, domestic cats were used to elucidate if they were definitive hosts of Spirometra species. Cats were orally fed with spargana recovered from naturally infected frogs and from experimentally infected hamster mice. The spargana fed to domestic cats developed into adult worms. Eggs discharged by the adult worms were collected from faeces of infected domestic cats. Cats were sacrificed, adult worms were recovered, and measurements and morphology of the worms were taken. All results were compatible with Spirometra species. Therefore, the study confirms that domestic cats are the definitive host of Spirometra species.